ILLOCUTIONARY ACTS AND MOTIVATIONAL FUNCTIONS IN DR. JILL BOLTE TAYLOR’S TED TALK MY STROKE OF INSIGHT - Muna Inarul Hida; Ruminda Ruminda; Hasbi Assiddiqi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study investigates how illocutionary acts function as motivational strategies in Dr. Jill Bolte Taylor’s TED Talk My Stroke of Insight. While previous studies have primarily focused on classifying speech acts, limited attention has been given to how illocutionary force contributes to the construction of motivational discourse in public speeches. Addressing this gap, the present research analyzes the intersection between linguistic action and motivational intent. Using a qualitative descriptive approach, 139 purposively selected utterances were examined based on their identifiable illocutionary force and motivational meaning. The analysis integrates Searle’s speech act framework with concepts of motivational communication, including emotional engagement, cognitive reframing, inspirational direction, supportive encouragement, and the strengthening of self-efficacy. The findings reveal that representative acts are the most dominant type, indicating the speaker’s emphasis on conveying information and personal insight. Emotional appeal appears as the most frequent motivational function, reflecting the talk’s strong affective orientation. Common combinations such as Representative + Emotional Appeal and Directive + Encouragement demonstrate how linguistic forms work synergistically with motivational strategies to enhance the persuasive and inspirational power of the message. This study contributes to a deeper understanding of how illocutionary acts shape motivational discourse in spoken communication.